LEGAL REVIEW ON DEADLINE FOR FILING A LAWSUIT BY THIRD PARTIES AT INDONESIAN STATE ADMINISTRATIVE COURT (PTUN) - Yogi Linel, Sepra; Nursyamsuddin, Nursyamsuddin; Mangihut, Mangihut; Syafrida, Syafrida (fakultas hukum universitas PGRI Semarang, 2024)
The time limit for filing a lawsuit in the State Administrative Court is an important part to pay attention to for parties who feel their interests have been harmed by the Decision of a State Administrative Body or Official. Not only for plaintiffs who need to consider the time limit as regulated in Article 55 of the Administrative Law, for third parties those whose interests are not addressed by the State Administration decision but whose interests are harmed also need to consider the grace period. Referring to SEMA No. 2 of 1991, a third party who feels their interests have been harmed must have a cumulative casuistry period calculated from the time the third party concerned feels their interests have been harmed and is aware of the existence of the State Administrative Decree. This research uses normative research methods so that the main study carried out by researchers is the statutory regulations relating to the research object.